2016
DOI: 10.1177/2049463716668905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fentanyl iontophoretic transdermal system and routine care with morphine intravenous patient-controlled analgesia in the management of early postoperative mobilisation: results from a randomised study

Abstract: Introduction: Fentanyl iontophoretic transdermal system (ITS) (IONSYS ® , The Medicines Company, Parsippany, NJ, USA) and morphine intravenous (IV) patient-controlled analgesia (PCA) have demonstrated equivalent pain control in several published studies. The primary objective of the current study was to compare fentanyl ITS with morphine IV PCA with regard to the patient's ability to mobilise with acute postoperative pain. Methods: In this multicentre, open-label, randomised, active-controlled, prospective pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…PCA use also has unwanted associated complications including ORAEs and delays in rehabilitation. Langford et al [16] demonstrated that PCA use versus an alternative fentanyl transdermal delivery poses delays in early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA use also has unwanted associated complications including ORAEs and delays in rehabilitation. Langford et al [16] demonstrated that PCA use versus an alternative fentanyl transdermal delivery poses delays in early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, these protocols vary widely between institutions with no current consensus on a standardized regimen. Preemptive analgesia [9], peripheral anesthesia techniques such as femoral nerve block (FNB) or adductor canal blocks [2], intraoperative periarticular injections (PAIs) [12] with mixed drug regimens or liposomal bupivacaine [3], patient-controlled analgesia (PCA), and oral narcotics [16,18] have all been part of reported regimens.…”
Section: Clinical Orthopaedics and Relatedmentioning
confidence: 99%
“…A multicenter, randomized open-label, phase IV clinical trial has also recently demonstrated that, at all time-points following surgery out to 24 hours, patients treated with the FITS were better able to mobilize than patients treated with IV morphine PCA 83 . Although the study was stopped and treatment terminated earlier than planned, patients in the FITS group (n ¼ 58) had a greater ability than those in the IV morphine PCA group (n ¼ 50) to mobilize at the time of stopping the study drug, with an adjusted mean ability to mobilize score (95% confidence intervals [CI] 0.14 (-0.19, 0.47) and 2.37 (1.98, 2.76) for the FITS and IV morphine PCA, respectively; p < .001) 83 .…”
Section: Fentanyl Iontophoretic Transdermal Systemmentioning
confidence: 99%
“…Para poder valorar la severidad del dolor en el posoperatorio, se debe tener en consideración el grado de la cirugía (menor, intermedia y mayor) 4 y la intensidad del dolor mediante una escala de medición 6,[16][17][18][19][20] . El manejo del dolor inadecuado es una de las condiciones de los países en desarrollo 4 .…”
Section: Introductionunclassified